If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4f + 10 = 2f + 22 Reorder the terms: 10 + 4f = 2f + 22 Reorder the terms: 10 + 4f = 22 + 2f Solving 10 + 4f = 22 + 2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2f' to each side of the equation. 10 + 4f + -2f = 22 + 2f + -2f Combine like terms: 4f + -2f = 2f 10 + 2f = 22 + 2f + -2f Combine like terms: 2f + -2f = 0 10 + 2f = 22 + 0 10 + 2f = 22 Add '-10' to each side of the equation. 10 + -10 + 2f = 22 + -10 Combine like terms: 10 + -10 = 0 0 + 2f = 22 + -10 2f = 22 + -10 Combine like terms: 22 + -10 = 12 2f = 12 Divide each side by '2'. f = 6 Simplifying f = 6
| tan(51)=x/8 | | 65x=20 | | 9.6/z=-3.2 | | (X+4)(x-2)=40 | | 5g+(-7)=-52 | | xa+5x-4=10 | | 4x(x+2)=6x | | -2.3q+16=-5g-38 | | y-4z=-42 | | 0=16t^2+104+56 | | -5x/3x= | | 4x^2-5y-100=0graph | | 4x^2y^2-2y^4-8xy^3+9x^3y+6y^4-2xy^3-3x^4+x^2y^2-3x^4= | | Y-23/3=-11 | | 4x^2-5y-100=0 | | C+3=4c-13 | | Y-20/3=-11 | | 48-(-4x)=7 | | 16x+9-17=(-3x)+7x | | 12-4-2= | | 6m+5(m+1)=26 | | r(x)=14 | | 7/16x=28 | | R*9/2=27 | | 5y=x+45 | | x^2-4x+5=-x^2+4x-1 | | W/1.02/3=-5 | | -21m+1=-7m+1 | | 4=(3x+1)-(16x-1) | | 2.3x+.5x=100 | | 20-3n=20-5n | | 3(-7x+8)=-165 |